2022
DOI: 10.1371/journal.pbio.3001775
|View full text |Cite
|
Sign up to set email alerts
|

Strong evidence for the adaptive walk model of gene evolution in Drosophila and Arabidopsis

Abstract: Understanding the dynamics of species adaptation to their environments has long been a central focus of the study of evolution. Theories of adaptation propose that populations evolve by “walking” in a fitness landscape. This “adaptive walk” is characterised by a pattern of diminishing returns, where populations further away from their fitness optimum take larger steps than those closer to their optimal conditions. Hence, we expect young genes to evolve faster and experience mutations with stronger fitness effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 107 publications
2
13
0
Order By: Relevance
“…In previous work using both divergence and polymorphism data, rapid evolution of mammalian-specific genes has been related to relaxed purifying selection but not to an increase in the proportion of adaptive substitutions (Gaya-Vidal and Alba 2014). In contrast, recent work using adaptive landscapes has shown that younger proteins in Drosophila and Arabidopsis are undergoing faster rates of adaptive evolution and tend to accumulate more substitutions with larger physicochemical effects than older proteins ( Moutinho et al 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…In previous work using both divergence and polymorphism data, rapid evolution of mammalian-specific genes has been related to relaxed purifying selection but not to an increase in the proportion of adaptive substitutions (Gaya-Vidal and Alba 2014). In contrast, recent work using adaptive landscapes has shown that younger proteins in Drosophila and Arabidopsis are undergoing faster rates of adaptive evolution and tend to accumulate more substitutions with larger physicochemical effects than older proteins ( Moutinho et al 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…These include only VIPs and non-VIPs with orthologs across mammals (Methods) since we previously showed that viruses increase adaptation more specifically in VIPs that are conserved across mammals and beyond (Castellano, 2019). This also limits the risk of confounding due to gene age (Moutinho et al, 2022). We compare VIPs with non-VIPs to highlight the evolutionary patterns that are specific to VIPs (Figure 1C,D).…”
Section: Resultsmentioning
confidence: 99%
“…As newly developed young genes perform either highly specialized (if generated de novo or via horizontal transfer) or redundancy (if generated via duplication) functions, they are more at risk of either losing their function or gaining novel functions in succeeding lineages (Domazet-Loso and Tautz, 2003;Daubin and Ochman, 2004;Wolf et al, 2009;Vishnoi et al, 2010). Though initially, young genes experience a large number of adaptive mutations, the substitution of some of the mutations will slowly optimize the function of the gene in due course of time and hence the supply of new adaptive mutations will also reduce; hence, ω value of a young gene will decline over time (Vishnoi et al, 2010;Moutinho et al, 2022). On the contrary, functions of old genes, like diabetic genes, are highly optimized and they are likely to have already exhausted all beneficial mutations by recent times and; thus, they are expected to evolve under negative selection and fix only neutral and/or nearly neutral mutations (Vishnoi et al, 2010).…”
Section: Codon Substitution Modelsmentioning
confidence: 99%